Method for manufacturing joined body, and method for manufacturing ceramic circuit board
Patent Information
- Application Number
- JP2024208568
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-02-17
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-26
AI Technical Summary
【0005】 実施形態にかかる接合体の製造方法では、ろう材を用いてセラミックス基板と銅板が加熱接合される。前記ろう材に含まれる原料の合計を100質量%とした場合に、前記ろう材は、Agを0質量%よりも高く75質量%以下、Cuを15質量%以上85質量%以下、TiまたはTiH2の1種または2種を合計1質量%以上15質量%以下、SnまたはInのいずれか1種を1質量%以上50質量%以下含有する。Agの平均粒径D50は、Cuの平均粒径D50よりも小さく、かつSnまたはInの平均粒径D50よりも小さい。前記ろう材は、示差走査熱量計(DSC)でDSC曲線を測定したときに、昇温工程の550℃以上700℃以下の範囲内に吸熱ピークを有する。
Smart Images

Figure 2025027095000001_ABST
Abstract
Description
[Technical field]
[0001] The embodiments described below relate to a method for manufacturing a bonded body and a method for manufacturing a ceramic circuit board. [Background technology]
[0002] A bonded body of a ceramic substrate and a copper plate is used as a circuit board on which a semiconductor element or the like is mounted. International Publication No. 2018 / 021472 (Patent Document 1) discloses a ceramic copper circuit board in which a ceramic substrate and a copper plate are bonded. In Patent Document 1, a brazing material containing Ag, Cu, Ti, etc. is used in the bonding layer. In addition, the TCT characteristics are improved by controlling the nanoindentation hardness of the bonding layer. In Patent Document 1, the nanoindentation hardness is controlled by having AgTi crystals or TiC present in the bonding layer. In Patent Document 1, the bonding strength and TCT characteristics are improved by controlling the nanoindentation hardness. In Patent Document 1, bonding is performed at a high bonding temperature of 780 to 850°C. High bonding temperatures increase the burden on bonding equipment. In addition, high-temperature bonding applies thermal stress to the ceramic substrate or copper plate. The thermal stress load causes distortion of the ceramic copper circuit substrate. For this reason, bonding at a lower temperature has been desired. For example, International Publication No. 2018 / 199060 (Patent Document 2) discloses a ceramic copper circuit board bonded at a bonding temperature of 720 to 800°C. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2018 / 021472 [Patent Document 2] International Publication No. 2018 / 199060 [Patent Document 3] Patent No. 5720839 Summary of the Invention [Problem to be solved by the invention]
[0004] In Patent Document 2, the bonding temperature is lower than in Patent Document 1, and therefore thermal stress is alleviated. On the other hand, since Patent Document 2 aims to diffuse Ag into the copper plate, the amount of Ag in the bonding brazing material is large. This results in a large cost burden. For example, Japanese Patent No. 5720839 (Patent Document 3) discloses a CuSnTi brazing material. Bonding is possible at 650°C with a brazing material that does not contain Ag. However, in Patent Document 3, the Ti material is sputtered, which is not suitable for large substrates. The present invention is intended to address these problems, and to provide a method for producing a bonded body and a method for producing a ceramic circuit board that enable bonding at low temperatures. [Means for solving the problem]
[0005] In the manufacturing method of the bonded body according to the embodiment, a ceramic substrate and a copper plate are heat-bonded using a brazing material. When the total amount of raw materials contained in the brazing material is taken as 100 mass%, the brazing material contains Ag in an amount of more than 0 mass% and 75 mass% or less, Cu in an amount of 15 mass% or more and 85 mass% or less, one or both of Ti and TiH2 in total in an amount of 1 mass% or more and 15 mass% or less, and either Sn or In in an amount of 1 mass% or more and 50 mass% or less. The average particle diameter D of Ag is 100 mass%. 50 is the average grain size of Cu, D 50 and the average grain size of Sn or In is smaller than D 50 The brazing filler metal has an endothermic peak in the range of 550° C. or more and 700° C. or less during the temperature rise step when a DSC curve is measured with a differential scanning calorimeter (DSC). [Brief description of the drawings]
[0006] [Figure 1] Schematic diagram illustrating a DSC curve. [Diagram 2] FIG. 2 is a diagram for explaining a method for calculating peak heights in a DSC curve. [Diagram 3] Temperature program for measuring the DSC graph. [Figure 4] 2 is an example of a DSC curve (450° C. or higher) in the temperature-raising step of Example 1. [Diagram 5] 2 is an example of a DSC curve (450° C. or higher) in the cooling step of Example 1. [Figure 6] 2 is an example of a DSC curve (450° C. or higher) in the temperature-raising step of Comparative Example 1. [Figure 7] 2 is an example of a DSC curve (450° C. or higher) in the cooling step of Comparative Example 1. [Figure 8] 1 is an example of a DSC curve (450° C. or higher) in the temperature-raising step of Example 2. [Figure 9] 1 is an example of a DSC curve (450° C. or higher) in the cooling step of Example 2. [Figure 10] 1 is an example of a DSC curve (550° C. or less) in the heating step of Example 3. [Figure 11] 1 is an example of a DSC curve (550° C. or less) in the cooling step of Example 3. [Figure 12] 1 is an example of a DSC curve (550° C. or less) in the heating step of Example 4. [Figure 13] 1 is an example of a DSC curve (550° C. or less) in the cooling step of Example 4. [Figure 14] 1 is an example of a DSC curve (550° C. or less) in the heating step of Example 5. [Figure 15] 1 is an example of a DSC curve (550° C. or less) in the cooling step of Example 5. [Figure 16] FIG. 2 is a diagram showing an example of a bonded body using a brazing material according to an embodiment. [Figure 17] FIG. 2 is a diagram showing an example of a ceramic circuit board using the brazing material according to the embodiment. [Figure 18] FIG. 2 is a diagram showing an example of a ceramic circuit board using the brazing material according to the embodiment. [Figure 19] FIG. 2 is a diagram showing an example of a ceramic circuit board using the brazing material according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] In one embodiment of the method for manufacturing a bonded body, a ceramic substrate and a copper plate are heat-bonded using a brazing material. When the total amount of raw materials contained in the brazing material is taken as 100 mass%, the brazing material contains Ag in an amount of more than 0 mass% and 75 mass% or less, Cu in an amount of 15 mass% or more and 85 mass% or less, one or both of Ti and TiH2 in total in an amount of 1 mass% or more and 15 mass% or less, and either Sn or In in an amount of 1 mass% or more and 50 mass% or less. The average particle diameter D of Ag is 100 mass%. 50 is the average grain size of Cu, D 50 and the average grain size of Sn or In is smaller than D 50 The brazing filler metal has an endothermic peak in the range of 550° C. or more and 700° C. or less during the temperature rise step when a DSC curve is measured with a differential scanning calorimeter (DSC).
[0008] The brazing material according to the embodiment is for joining a ceramic substrate and a metal plate. Examples of the ceramic substrate include a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, and an aluminium substrate. The aluminium substrate is a substrate in which aluminum oxide and zirconium oxide are mixed. Examples of the metal plate include a copper plate and an aluminum plate. The copper plate is not limited to a pure copper plate, and may be a copper alloy plate. Examples of the copper plate include those shown in JIS-H-3100. Among these, oxygen-free copper (copper purity of 99.96 wt% or more) is preferred.
[0009] The brazing material is preferably an active metal brazing material. The active metal is one selected from Ti (titanium), Zr (zirconium), and Hf (hafnium). A joining method using an active metal brazing material is called an active metal joining method. Among the active metals, Ti is preferable. Ti is a more active metal than Zr and Hf. The cost of Ti is also lower than Zr and Hf. The active metal may be added to the brazing material not only as a simple metal but also as a compound. Examples of the compound include hydrides, oxides, and nitrides. The joining method using active metal brazing material is called the active metal joining method. In the active metal joining method, an active metal brazing material is placed between a ceramic substrate and a metal plate, and then the two are heated to join to produce a joined body. The active metal brazing material becomes a joining layer through the heated joining. In other words, the active metal brazing material corresponds to the brazing material before joining. The joining layer indicates the state after joining. In the active metal bonding method, the active metal reacts with the ceramics to form a reaction layer. When Ti (titanium) is used as the active metal, the Ti reacts with the ceramic substrate to form a Ti reaction layer. When a nitride ceramic substrate is used, a Ti reaction layer is formed with titanium nitride (TiN) as the main component. When an oxide ceramic substrate is used, a Ti reaction layer is formed with titanium oxide (TiO2) as the main component. The nitride ceramic substrate refers to a silicon nitride substrate or an aluminum nitride substrate. The oxide ceramic substrate refers to an aluminum oxide substrate or an aluminium substrate. A part of the active metal brazing material layer may be diffused into the metal plate by thermal bonding. The brazing material preferably contains one or more selected from Ag (silver), Cu (copper), Sn (tin), In (indium), and C (carbon) as a component other than the active metal. Ag or Cu is a component that becomes the base material of the brazing material. Sn or In has the effect of lowering the melting point of the brazing material. C has the effect of controlling the fluidity of the brazing material and controlling the structure of the bonding layer by reacting with other components. For this reason, the components of the brazing material include Ag-Cu-Ti, Ag-Cu-Sn-Ti, Ag-Cu-Ti-C, Ag-Cu-Sn-Ti-C, Ag-Ti, Cu-Ti, Ag-Sn-Ti, Cu-Sn-Ti, Ag-Ti-C, Cu-Ti-C, Ag-Sn-Ti-C, and Cu-Sn-Ti-C. In place of Sn, In may be used. Both Sn and In may be used. Instead of Sn or In, a low melting point metal such as Bi (bismuth), Sb (antimony), or Ga (gallium) may be used.
[0010] First, the DSC curve of the brazing material is measured using a differential scanning calorimetry (DSC). A differential scanning calorimetry applies heat to a sample and measures whether or not an endothermic or exothermic reaction occurs. When an endothermic or exothermic reaction occurs, a peak appears on the DSC curve. A negative peak indicates an endothermic reaction. A positive peak indicates an exothermic reaction. An endothermic reaction indicates that the sample is melting or decomposing. An exothermic reaction indicates that the constituent elements of the sample are reacting with each other to form or solidify a compound (including alloying). The larger the peak, the greater the heat of reaction. Here, a negative peak is called an endothermic peak, and a positive peak is called an exothermic peak. The apex of the peak is called the peak top. The difference between the maximum and minimum points of the peak is called the peak height.
[0011] FIG. 1 is a schematic diagram illustrating a DSC curve. In Figure 1, the horizontal axis indicates temperature (°C) and the vertical axis indicates heat flux (mW / mg). In the example of Figure 1, a positive peak occurs at 300°C. This indicates that an exothermic reaction occurs at 300°C. Also, a negative peak occurs at 600°C. This indicates that an endothermic reaction occurs at 600°C.
[0012] FIG. 2(a) and FIG. 2(b) are diagrams for explaining a method for calculating the peak height in a DSC curve. In FIG. 2(a), a peak in the positive direction is illustrated. In FIG. 2(b), a peak in the negative direction is illustrated. As shown in FIG. 2(a) and FIG. 2(b), a baseline extension B1 is generated to the left of the peak (left as you look at the paper). The baseline extension B1 is a horizontal line from the left root of the peak (the so-called peak start). A tangent T1 is generated as the longest straight line along the left side of the peak. An intersection X between the baseline extension B1 and the tangent T1 is generated. A baseline extension B2 is generated to the right of the peak (right as you look at the paper). The baseline extension B2 is a horizontal line from the right root of the peak (the so-called peak end). A tangent T2 is generated as the longest straight line along the right side of the peak. An intersection Y between the baseline extension B2 and the tangent T2 is generated. An intersection M between the XY straight line connecting the intersection X and the intersection Y and a line vertically dropped from the peak top P to the horizontal axis is generated. The distance between the intersection point M and the peak top P is defined as the peak height H. Here, peaks with a peak height H of 0.01 mW / mg or more during temperature increase and decrease are extracted as peaks.
[0013] For example, an endothermic peak is in the negative direction, so it goes up, down, and up again. The endothermic peak goes from maximum to minimum to maximum. This minimum point (the lowest point) is the peak top. Also, of the maximum points on the low temperature and high temperature sides of the minimum point, the larger one is considered to be the maximum point. The peak height is the value obtained by subtracting the minimum point from the maximum point. Since the heat generation peak is in the positive direction, it goes down, up, and down. The heat generation peak goes from minimum point to maximum point to minimum point. This maximum point (the point where it has risen the most) is the peak top. Also, of the minimum points on the low temperature and high temperature sides of the maximum point, the one with the larger value is considered to be the minimum point. The peak height is the maximum point minus the minimum point. In addition, the end point of an endothermic peak (a peak in the negative direction) may appear to be an exothermic peak (a peak in the positive direction), but it is counted as an exothermic peak here. Also, it is acceptable to draw an extension of the baseline to find each peak.
[0014] FIG. 3 shows a temperature program for measuring a DSC curve. In FIG. 3, the horizontal axis shows time (minutes) and the vertical axis shows temperature (°C). In the temperature-raising step, the temperature is raised from room temperature to 500°C at a rate of 5°C / min. Next, in the temperature-raising step, 500°C is held for 60 minutes. Next, in the temperature-raising step, the temperature is raised to 845°C at a rate of 5°C / min. Thereafter, the temperature of 845°C is held for 30 minutes. In the temperature-lowering step, the temperature is lowered from 845°C to room temperature at a rate of 5°C / min. As the DSC, a NETZSCH TGA-DSC simultaneous thermal analyzer STA449-F3-Jupiter or an apparatus having equivalent performance can be used. The measurement is performed in an Ar (argon) flow by dropping an appropriate amount of brazing material into an alumina container. It is necessary to prevent the brazing material from reacting with the atmosphere by measuring in an Ar atmosphere. The flow rate of the Ar flow is set to 20 ml / min on the sample side and 200 ml / min on the cooling side. The amount (mg) dropped is measured with a balance. The above method is used to measure a DSC curve in the range of 100°C to 845°C. In other words, a DSC curve is a profile obtained by plotting the change in heat flux against temperature using a DSC. The DSC written on the vertical axis of the DSC curve indicates the heat flux measured by DSC. It is also preferable to measure the DSC curve of the brazing material before the joining step is performed. When measuring the DSC curve of the joined body, the measurement is performed using a sample in which the joining layer is separated from the joined body. The bonding layer in the bonded body exists between the ceramic substrate and the metal plate. When preparing a sample by separating the bonding layer from the bonded body, the ceramic substrate and the metal plate should not be included. The Ti reaction layer present on the ceramic substrate surface may be included in the bonding layer. If it is difficult to cut at the boundary between the ceramic substrate and the Ti reaction layer, a part of the Ti reaction layer may be included in the sample. In addition, the active metal brazing material is bonded to the metal plates while diffusing into them. When preparing a sample by separating the bonding layer from the bonded body, the area where the active metal brazing material diffused into the metal plates should not be included. In other words, only the bonding layer portion is used as the measurement sample. For example, when copper plates are joined using an Ag-Cu-Ti active metal brazing material, the brazing material diffuses into the copper plate. Because Cu is used as a brazing material component, it may be difficult to distinguish the boundary between the joining layer and the copper plate. For this reason, the boundary is set to within 20 μm from the Ti reaction layer toward the copper plate. The sample to be cut out is set to 1 g.
[0015] The brazing filler metal according to the embodiment is characterized in that it has an endothermic peak in the range of 550° C. or more and 700° C. or less during the temperature rising process. FIG. 4 shows a DSC curve in the temperature rise step of Example 1. In FIG. 4, the horizontal axis shows temperature (°C) and the vertical axis shows heat flux (mW / mg). Heat flux is abbreviated as DSC. FIG. 4 shows the range of 450°C or higher in the DSC curve of 100°C or higher and 845°C or lower. In the embodiment, peaks with a peak height of 0.01 mW / mg or higher were counted. In FIG. 4, endothermic peaks are detected at 498° C., 606° C., 671° C., and 713° C. Also, exothermic peaks are detected at 581° C. and 619° C. Although not shown, as shown in Table 3, endothermic peaks are also detected at 172° C. and 498° C. Similarly, an exothermic peak is detected at 224° C. In Figure 4, two endothermic peaks are detected in the temperature rise process within the range of 550°C to 700°C. The endothermic reaction indicates that the brazing material is melting or decomposing. The occurrence of endothermic peaks within the temperature range of 550°C to 700°C indicates that the brazing material is melting in this temperature range. The melting of the brazing material indicates that a joining reaction is occurring. At least one of the endothermic peaks at 550 to 700°C has a height of preferably 0.04 mW / mg or more. The peak height indicates the magnitude of the reaction. By having a large endothermic peak, bonding can be achieved in this temperature range. For this reason, the peak height is preferably 0.04 mW / mg or more, more preferably 0.07 mW / mg or more.
[0016] The brazing material preferably contains Ag (silver), Cu (copper) and Ti (titanium). The brazing material containing Ag, Cu and Ti is a type of active metal brazing material. The active metal brazing material can firmly bond the ceramic substrate and the copper plate. The brazing material has an endothermic peak at 550 to 700°C during the heating process, so that the bonding temperature can be reduced to 800°C or less. In addition, the brazing material preferably has two or more endothermic peaks in the range of 550°C to 650°C in the temperature rise process. Even if there is only one endothermic peak, bonding is possible. Having two or more endothermic peaks indicates that the melting reaction occurs in multiple stages. The occurrence of melting in multiple stages changes the bonding layer and advances the reaction. In addition, it is preferable that at least one of the endothermic peaks between 550 and 650°C has a peak height of 0.04 mW / mg or more.
[0017] In addition, when comparing the endothermic peak at 550 to 650°C in the temperature-raising step with the endothermic peak at 700°C or higher, it is preferable that the endothermic peak at 550 to 650°C is larger. That is, the peak height of the endothermic peak at 550 to 650°C in the temperature-raising step is larger than the peak height of the endothermic peak at 700°C or higher in the temperature-raising step. When there are two or more endothermic peaks in the range of 550 to 650°C, the largest peak among them is used as the reference. When there are two or more endothermic peaks at 700°C or higher, the peak with the largest peak height among them is used as the reference. The peak with the largest peak height is called the maximum peak. The fact that the endothermic peak at 550 to 650°C is larger indicates that no significant melting reaction occurs at 700°C or higher. In addition, when comparing the peak height ratio, the ratio is preferably 2 or more. The ratio is expressed as (peak height of the largest endothermic peak at 550 to 650°C) / (peak height of the largest endothermic peak at 700°C or higher). When the peak ratio is 2 or more, it can be said that the main melting reaction is completed within the range of 550 to 650°C. In addition, the smaller the peak height of the endothermic peak at 700°C or higher, the better. Most preferably, there is no endothermic peak at 700°C or higher. The smaller the endothermic peak at 700°C or higher, the less the melting reaction occurs. In other words, the smaller the endothermic peak at 700°C or higher, the more the melting reaction is almost completed at 700°C or lower, and even at 550 to 650°C.
[0018] The brazing material preferably has an endothermic peak in the range of 450°C to 520°C in the heating process. In addition, the endothermic peak preferably has a peak height of 0.07mW / mg or more in the range of 450°C to 520°C. When TiH2 (titanium hydride) is added to the brazing material to contain Ti, a reaction occurs in the range of 450 to 520°C in which Ti decomposes into Ti and H. This decomposition reaction is the main endothermic reaction. The hydrogen after decomposition has the effect of removing oxygen in the brazing material or activating the metal components. When a substance other than a hydride, such as Ti alone, is added, this endothermic peak may not be present. The brazing material preferably has an endothermic peak or an exothermic peak, or both, in the range of 140°C to 300°C in the DSC curve of the heating step. In addition, the peak height of either the endothermic peak or the exothermic peak in the range of 140°C to 300°C is preferably 0.04 mW / mg or more. FIG. 10 shows a DSC curve of the heating step of Example 3. FIG. 10 shows the range of 550°C or less in the DSC curve of 100°C to 845°C. As shown in Table 3 below, there are endothermic peaks at 172°C and 220°C. In addition, exothermic peaks were detected at 217°C and 232°C. In order to generate an endothermic peak or an exothermic peak in the range of 140°C to 300°C in the temperature rise step, it is preferable to include Sn (tin) in the brazing material. For example, when Sn is included in an Ag-Cu-Ti brazing material, an endothermic reaction occurs due to the melting of Sn, and an exothermic reaction occurs due to the formation of an SnAg compound or an SnCu compound. By generating an endothermic peak or an exothermic peak at a temperature lower than the endothermic reaction (melting reaction) of 550 to 650°C, the reaction can be promoted in multiple stages. This allows the thermal stress to be alleviated. In particular, it is preferable that there is an exothermic peak. Also, the height of the exothermic peak is preferably 0.04 mW / mg or more. This indicates that the reaction to form the SnAg compound or SnCu compound has progressed sufficiently. Therefore, the height of the exothermic peak is preferably 0.04 mW / mg or more, more preferably 0.05 mW / mg or more.
[0019] In the DSC curve of the temperature lowering step, it is preferable that the peak in the range of 140 ° C. or more and 300 ° C. or less is small. The fact that the peak in the range of 140 ° C. or more and 300 ° C. or less in the temperature lowering step is small indicates that the reaction of forming the SnAg compound or the SnCu compound hardly occurs. In other words, it indicates that the reaction of forming the SnAg compound or the SnCu compound in the temperature raising step is sufficiently promoted. In addition, the peak is small means that the peak is not detected or the peak height is less than 0.04 mW / mg. It is most preferable that the peak is not detected in the range of 140 ° C. or more and 300 ° C. or less in the DSC curve of the temperature lowering step. FIG. 11 shows the DSC curve of the temperature lowering step of Example 3. FIG. 11 shows 550 ° C. or less among the DSC curves of 100 ° C. or more and 845 ° C. or less. In addition, as shown in Table 3 described later, in the DSC curve of the temperature lowering step of Example 3, no peak was detected in the range of 140 ° C. or more and 300 ° C. or less. In addition, it is preferable that the exothermic peak occurs at 400°C or more and 700°C or less in the temperature lowering process. In addition, it is preferable that the maximum exothermic peak in the temperature lowering process is in the range of 500 to 650°C. The exothermic peak in the temperature lowering process occurs due to the formation of a compound (alloy) or solidification of the bonding layer. The thermal stress generated when the molten brazing material solidifies is the largest. This is because after the bonding interface is formed, materials with different thermal expansion coefficients are constrained to each other, and stress occurs due to the difference in thermal expansion during cooling. If the maximum exothermic peak in the temperature lowering process is less than 500°C, the solidification temperature is too low and the reliability of the bond may decrease. On the other hand, if it is higher than 650°C, the thermal stress may become excessively large. It is important that the maximum peak of the heat generation peak in the temperature-lowering process is within the range of 500 to 650°C. By completing the main solidification reaction by 500°C in the temperature-lowering process, thermal stress can be alleviated. The bonding layer of the completed bonded body does not need to be a completely molten structure, and may be a partially molten structure. A partially molten bonding layer is a mixture of a molten structure and an unmelted structure. The unmelted structure is also called a melted and separated structure. In addition, the temperature at which the exothermic peak top occurs in the temperature-lowering step from 400° C. to 700° C. is preferably at least 10° C. lower than the temperature at which the endothermic peak top occurs in the temperature-higher step from 400° C. to 700° C. By lowering the peak top temperature in the temperature-lowering step, the occurrence of thermal stress in the temperature-lowering step can be suppressed.
[0020] In addition, the brazing material preferably has an exothermic peak in the range of 450°C to 520°C in the DSC curve in the temperature lowering step. The exothermic peak is a positive peak. The endothermic peak in the range of 450 to 520°C in the temperature raising step is mainly due to the decomposition reaction of TiH2. In contrast, the exothermic peak in the temperature lowering step is due to the solidification of the bonding layer or the exothermic reaction for forming a Ti compound. Examples of Ti compounds include TiN (titanium nitride), AgTi, CuTi, and TiC. Ti is an active metal. The bonding property is more stable when Ti compounds are present in the bonding layer than when Ti exists as a simple substance.
[0021] FIG. 5 shows the DSC curve of the temperature lowering step of Example 1. FIG. 5 shows the range of 450°C or more. In FIG. 5, exothermic peaks are detected at 477°C, 602°C, 644°C, and 688°C. In the DSC curve of the temperature lowering step, no peak is detected within the range of 140°C or more and 300°C or less. This indicates that the formation of SnAg or SnCu is promoted in the temperature increasing step. In addition, the maximum exothermic peak is detected at 500 to 650°C in the temperature lowering step.
[0022] The brazing material composition preferably contains 0% to 75% by mass of Ag (silver), 15% to 85% by mass of Cu (copper), and 1% to 15% by mass of Ti (titanium) or TiH2 (titanium hydride). When both Ti and TiH2 are used, the total is within the range of 1% to 15% by mass. When both Ag and Cu are used, it is preferable that Ag is 20 to 60% by mass and Cu is 15 to 40% by mass. The brazing material composition may contain one or both of Sn (tin) and In (indium) in an amount of 1% by mass to 50% by mass, if necessary. The content of Ti or TiH2 is preferably 1% by mass to 15% by mass, more preferably 1% by mass to 6% by mass. If the content of Ti is 6% by mass or less, the combination with Sn or In makes it easy to generate two or more endothermic peaks in the range of 550 to 650°C. If necessary, C (carbon) may be contained in an amount of 0.1% by mass to 2% by mass. The ratio of the brazing material composition is calculated with the total of the mixed raw materials being 100% by mass. For example, if the brazing material is composed of three elements, Ag, Cu, and Ti, then Ag+Cu+Ti=100% by mass. If the brazing material is composed of four elements, Ag, Cu, TiH2, and In, then Ag+Cu+TiH2+In=100% by mass. If the brazing material is composed of five elements, Ag, Cu, Ti, Sn, and C, then Ag+Cu+Ti+Sn+C=100% by mass.
[0023] The mass ratio Ag / Cu in the brazing filler metal composition is preferably 1.3 or less. The endothermic peak at 550 to 700 °C in the heating process is a reaction that melts the brazing filler metal components to form a liquid phase. The mass ratio Ag / Cu in a general active metal brazing filler metal is 2.3 (= 7 / 3). This ratio is for forming the AgCu eutectic. When the mass ratio Ag / Cu is 2.3, no endothermic peak is formed at 550 to 700 °C. This is because the liquid phase formation temperature becomes high. The mass ratio Sn / Ag in the brazing filler metal composition is preferably 0.25 or more. Also, the mass ratio In / Ag is preferably 0.25 or more. By setting it within this range, an exothermic peak can be formed at 140 to 300 °C in the heating process. The peak at 140 to 300 °C in the heating process indicates an endothermic reaction in which Sn melts and an exothermic reaction in which SnAg or SnCu is formed. By increasing the formation amount of SnAg or SnCu, the liquid phase formation temperature can be set to around 600 °C. Thereby, the endothermic peak at 550 to 700 °C can be increased. The same applies when using a low melting point metal such as In instead of Sn. C (carbon) has the effect of lowering the solidification temperature of the bonding layer in the cooling process. Thereby, the generation temperature of the peak top of the exothermic peak at 400 °C or higher and 700 °C or lower in the cooling process can be 10 °C or more lower than the generation temperature of the peak top of the endothermic peak at 400 °C or higher and 700 °C or lower in the heating process.
[0024] The average particle diameter D of the Ag powder used as the raw material of the brazing filler metal 50 is preferably 3.0 μm or less, and more preferably 2.0 μm or less. The average particle diameter D of the Cu powder 50 is preferably 6.0 μm or less, and more preferably 4.0 μm or less. The average particle diameter D of the Ti powder or TiH2 powder 50 is preferably 6.0 μm or less, and more preferably 4.0 μm or less. The average particle diameter D of the Sn powder or In powder 50 is preferably 6.0 μm or less, and more preferably 4.0 μm or less. The average particle diameter D of the C powder 50 is preferably 6.0 μm or less, and more preferably 4.0 μm or less. The average particle diameter D of the Ag powder 50 <The average particle diameter D of the Cu powder50 is preferably. The average particle size D of the Ag powder 50 <is the average particle size D of the Sn powder or the In powder 50 is preferably. The average particle size D of the Cu powder 50 <is the average particle size D of the Sn powder or the In powder 50 is preferably. By reducing the particle size of the Ag powder, the contact ratio between the Ag powder and other powders can be increased. As a result, the endothermic peak at 550 to 700 °C can be increased. Alternatively, the endothermic peak or exothermic peak at 140 to 300 °C can be increased.
[0025] The brazing material as described above is suitable for a bonded body obtained by bonding a ceramic substrate and a metal plate. Examples of the ceramic substrate include a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, and an aludur substrate. The thickness of the ceramic substrate is preferably 0.1 mm or more and 1 mm or less. If the substrate thickness is less than 0.1 mm, the strength may decrease. On the other hand, if it is thicker than 1 mm, the ceramic substrate becomes a heat resistor, and the heat dissipation of the ceramic copper circuit board may decrease. The silicon nitride substrate preferably has a three-point bending strength of 600 MPa or more. Also, the silicon nitride substrate preferably has a thermal conductivity of 80 W / m·K or more. By increasing the strength of the silicon nitride substrate, the substrate thickness can be reduced. Therefore, the three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more, more preferably 700 MPa or more. The substrate thickness of the silicon nitride substrate can be made thinner to 0.40 mm or less, more preferably 0.30 mm or less. The three-point bending strength of the aluminum nitride substrate is about 300 to 450 MPa. On the other hand, the thermal conductivity of the aluminum nitride substrate is 160 W / m·K or more. Since the aluminum nitride substrate has low strength, the substrate thickness is preferably 0.60 mm or more. The aluminum oxide substrate has a three-point bending strength of about 300 to 450 MPa, but is inexpensive. The three-point bending strength of the aludur substrate is as high as about 550 MPa, but the thermal conductivity is about 30 to 50 W / m·K. A silicon nitride substrate is preferable as the ceramic substrate, since the strength of the silicon nitride substrate is high and excellent reliability can be obtained even when a thick copper plate is bonded to the silicon nitride substrate.
[0026] Examples of the metal plate include a copper plate and an aluminum plate. The metal plate is preferably a copper plate. The copper plate preferably has a thickness of 0.6 mm or more. The thermal conductivity of the copper plate is about 400 W / m·K. By making the copper plate thicker, the heat dissipation of the circuit board can be improved. For this reason, the thickness of the copper plate is preferably 0.6 mm or more, and further preferably 0.8 mm or more. In addition, since the silicon nitride substrate has high strength, it is possible to obtain excellent reliability even when a thick copper plate is bonded. In other words, a silicon nitride copper circuit board in which a silicon nitride substrate having a substrate thickness of 0.40 mm or less and a three-point bending strength of 600 MPa or more is bonded to a copper plate having a thickness of 0.6 mm or more is a preferred combination.
[0027] According to the manufacturing method of the bonded body of the embodiment, the bonding temperature can be set to 800°C or less. Also, bonding can be performed at or above the maximum peak temperature of the endothermic peak present at 550 to 650°C in the heating process of the brazing material. That is, the bonding temperature is equal to or above the maximum peak temperature of the endothermic peak present at 550 to 650°C in the heating process. The difference between the bonding temperature and the maximum peak temperature is preferably 50°C or more and 100°C or less. As described above, the brazing material preferably has an endothermic peak at 550 to 650°C. For example, if the largest endothermic peak is 600°C, the bonding temperature is preferably set to a range of 650 to 700°C. Even in this case, bonding at a temperature higher than 700°C is possible. On the other hand, the higher the bonding temperature, the greater the thermal stress. Thermal stress is deformation caused by not only reaction and solidification of the brazing material but also grain growth of the copper plate. By lowering the bonding temperature, the thermal stress can be reduced. By reducing the thermal stress, the warping of the bonded body of the ceramic substrate and the copper plate can be reduced. Furthermore, a circuit pattern can be formed on the metal plate of the bonded body to produce a ceramic circuit board. The circuit pattern can be formed by an etching process.
[0028] If the copper plate is made thicker, the thermal stress caused by the copper plate will increase. Also, by increasing the size of the ceramic substrate, multiple pieces can be obtained. Multiple pieces are obtained by cutting a large bonded body to obtain small bonded bodies. There are also methods of dividing the bonded body or dividing the ceramic circuit substrate. To make it easier to divide, scribing may be performed. According to the bonded body of the embodiment, even if the ceramic substrate size is increased to 200 mm or more in length and 200 mm or more in width, the warping of the bonded body can be reduced. Therefore, it is possible to achieve both an increase in the ceramic substrate size and an increase in the thickness of the copper plate. In particular, by setting the strength of the silicon nitride substrate to 600 MPa or more, the warping of the bonded body can be reduced even if the substrate thickness is reduced to 0.40 mm or less. The copper plate to be bonded may be preliminarily processed into a circuit shape, or may be a solid copper plate. The solid copper plate is etched after bonding. Copper plates may be bonded to both sides of a ceramic substrate. When copper plates are bonded to both sides, one side may be a circuit and the other side a heat sink, or both may be circuits. When copper plates are bonded to both sides, it is preferable that the thickness of one side is 0.6 mm or more.
[0029] (Example) (Examples 1 to 6, Comparative Example 1) The brazing material compositions prepared were shown in Tables 1 and 2. Table 1 shows the particle size of the raw material powder. TiH2 powder was used as the Ti component.
[0030] [Table 1]
[0031] [Table 2]
[0032] The brazing material components according to the examples and comparative examples were mixed with a resin binder to prepare brazing material pastes. A DSC curve was measured for each brazing material paste using a differential scanning calorimeter. The DSC measurement device used was a NETZSCH TGA-DSC simultaneous thermal analysis device STA449-F3-Jupiter. The measurement was performed in an Ar flow with an appropriate amount of brazing material dropped into an alumina container. The Ar flow rate during the measurement was set to 20 ml / min on the sample side and 200 ml / min on the cooling side. The temperature program was set to the conditions shown in Figure 3. DSC curves were measured in the range of 100°C to 845°C. The detection temperatures of the endothermic peak and the exothermic peak in the temperature increasing step and the temperature decreasing step are shown in Table 3.
[0033] [Table 3]
[0034] FIG. 4 shows an example of a DSC curve (450° C. or higher) in the temperature increasing step of Example 1. FIG. 5 shows an example of a DSC curve (450° C. or higher) in the temperature decreasing step of Example 1. FIG. 6 shows an example of a DSC curve (450° C. or higher) in the temperature increasing step of Comparative Example 1. FIG. 7 shows an example of a DSC curve (450° C. or higher) in the temperature decreasing step of Comparative Example 1. FIG. 8 shows an example of a DSC curve (450° C. or higher) in the temperature increasing step of Example 2. FIG. 9 shows an example of a DSC curve (450° C. or higher) in the temperature decreasing step of Example 2. FIG. 10 shows an example of a DSC curve (550° C. or lower) in the temperature increasing step of Example 3. FIG. 11 shows an example of a DSC curve (550° C. or lower) in the temperature decreasing step of Example 3. FIG. 12 shows an example of a DSC curve (550° C. or lower) in the temperature increasing step of Example 4. FIG. 13 shows an example of a DSC curve (550° C. or lower) in the temperature decreasing step of Example 4. Fig. 14 shows an example of a DSC curve (550°C or less) in the temperature increasing step of Example 5. Fig. 15 shows an example of a DSC curve (550°C or less) in the temperature decreasing step of Example 5. In Comparative Example 1 (FIG. 6), no endothermic peak was detected in the range of 550 to 700°C in the heating process. In contrast, in the brazing material according to the embodiment, an endothermic peak was detected in the range of 550 to 700°C. When comparing the endothermic peak at 550 to 700°C with the endothermic peak in the range exceeding 700°C, the endothermic peak in the range exceeding 700°C was smaller. This indicates that the melting reaction of the brazing material is promoted in the range of 550 to 700°C. Moreover, in Comparative Example 1 (FIG. 7), no exothermic peak was detected in the range of 500 to 650°C. In Examples 2, 4, and 5, two or more endothermic peaks were detected within the range of 550 to 650°C. At least one of the two endothermic peaks detected had a peak height of 0.07 mW / mg or more. In Examples 2, 4, and 5, no endothermic peak was detected at a temperature exceeding 700°C.
[0035] Next, the brazing material of the example and the comparative example was used to perform a joining process between the ceramic substrate and the copper plate. As the ceramic substrate, a silicon nitride substrate 1 with a thermal conductivity of 90 W / m·K, a three-point bending strength of 700 MPa, and a plate thickness of 0.32 mm was prepared. In addition, a silicon nitride substrate 2 with a thermal conductivity of 85 W / m·K, a three-point bending strength of 650 MPa, and a plate thickness of 0.25 mm was prepared. An aluminum nitride substrate with a thermal conductivity of 170 W / m·K, a three-point bending strength of 400 MPa, and a plate thickness of 0.635 mm was prepared. Oxygen-free copper was used as the copper plate. A copper plate 1 with a thickness of 0.6 mm, a copper plate 2 with a thickness of 0.8 mm, and a copper plate 3 with a thickness of 0.3 mm were prepared. The size of the ceramic substrate was 250 mm long x 200 mm wide. Solid copper plates were bonded to both sides of the ceramic substrate. The amount of warping of the bonded body obtained was measured. The bonding strength of the copper plates was also measured. The amount of warping of the bonded body was measured on the long side. The amount of warping of the ceramic substrate was observed from the side of the bonded body. A straight line was drawn between the ends of the long sides of the ceramic substrate. The farthest point between the straight line and the surface of the ceramic substrate was taken as the amount of warping. Joints with a warp of 0.1 mm or less on the long side were marked as good (◯), and joints with a warp of more than 0.1 mm were marked as defective (×). The bonding strength was measured by a peel test. Specifically, a peel test sample was prepared using the bonding conditions of each Example and Comparative Example. The sample was prepared by bonding a rectangular copper plate to a ceramic substrate. At that time, the copper plate was bonded so that one end of the copper plate protruded from the ceramic substrate. The protruding copper plate was pulled vertically to measure the peel strength. Joints with a joint strength of 20 kN / m or more were rated as the best product (◎), those with a joint strength of 15 kN / m or more were rated as good products (◯), and those with a joint strength of 14 kN / m or less were rated as poor products (×). Table 4 shows the results.
[0036] [Table 4]
[0037] For the bonded bodies according to the embodiment, the amount of warping was reduced even when the bonding temperature was 800°C or less. In addition, high bonding strength was obtained. It was found that bonding can be performed at a low temperature by controlling the endothermic peak and exothermic peak in the DSC curve of the brazing material. In contrast, in Comparative Example 1A, the bonding strength was high when the bonding temperature was 850°C, but the warping was large. This was because the thermal stress caused by bonding at high temperatures was large. Furthermore, when the bonding temperature was lowered as in Comparative Example 1B, the bonding strength decreased.
[0038] As a reference example, a silicon nitride substrate with a size of 50 mm length x 50 mm width x 0.32 mm thickness was prepared. A copper plate with a size of 50 mm length x 50 mm width x 0.6 mm thickness was prepared. The brazing material of Example 1 and Comparative Example 1 was used to perform bonding at a bonding temperature of 850°C. The warpage and bonding strength were judged to be good. In other words, even with the conventional brazing material, if the bonded body is small, the warpage can be reduced. On the other hand, if the bonded body is large, 200 mm x 200 mm or more, the warpage becomes large. If the brazing material of the example is used, the bonding temperature can be lowered, the warpage can be reduced, and the bonding strength can be maintained. Therefore, the brazing material of the example has excellent mass productivity for the bonded body.
[0039] (zygote) FIG. 16 is a diagram showing an example of a bonded body using the brazing material according to the embodiment. In FIG. 16, 10 is a ceramic circuit board. 12 is a ceramic substrate. 13 is a front metal plate. 14 is a bonding layer. 15 is a back metal plate. Each of the front metal plate 13 and the back metal plate 15 is bonded to the ceramic substrate 12 via the bonding layer 14. The brazing material according to the embodiment is suitable for the bonded body shown in FIG. 16. By using the brazing material according to the embodiment, for example, the reliability of the bonded body can be improved. In addition, when a circuit shape is given to the front metal plate 13 or the back metal plate 15 of the bonded body, a ceramic circuit board 10 is obtained. In addition, in the bonded body, the vertical and horizontal sizes of the front metal plate 13 or the back metal plate 15 may be the same as those of the ceramic substrate 12. The circuit shape can be given by using an etching process or the like.
[0040] (Joints and ceramic circuit boards) 17 to 19 are diagrams showing an example of a ceramic circuit board using the brazing material according to the embodiment. 17, two front metal plates 13 processed into a circuit shape are bonded to a ceramic substrate 12. The embodiment is not limited to this example, and three or more front metal plates 13 may be bonded to the ceramic substrate 12. The ceramic substrate may have a through hole. The ceramic circuit substrate preferably has a structure in which the front metal plate and the rear metal plate are electrically connected through the through hole. FIG. 18 shows an example of a ceramic circuit substrate having a through hole. FIG. 18 is a cross-sectional view of a portion in which a through hole is provided. In FIG. 18, 10a is a ceramic circuit substrate. 12 is a silicon nitride substrate. 13 is a front metal plate. 14 is a bonding layer. 18 is a rear metal plate. 19 is a through hole. In FIG. 18, the front metal plate 13 and the rear metal plate 18 are electrically connected through the through hole 19. In FIG. 18, a plurality of through holes 19 respectively connect a plurality of front metal plates 13 and a plurality of rear metal plates 18. The embodiment is not limited to such a structure. In the ceramic circuit substrate 10a, the through hole 19 may be provided only in a portion of the plurality of front metal plates 13. The through hole 19 may be provided only in a portion of the plurality of rear metal plates 18. The inside of the through hole 19 is preferably filled with the same material as the bonding layer 14. The internal structure of the through hole 19 is not particularly limited as long as it can electrically connect the front metal plate and the back metal plate. For this reason, a metal thin film may be provided only on the inner wall of the through hole 19. On the other hand, by filling the through hole 19 with the same material as the bonding layer 14, the bonding strength can be improved. The silicon nitride circuit board according to the embodiment is suitable for a semiconductor device. In the semiconductor device, a semiconductor element is mounted on a metal plate of a ceramic circuit board via a bonding layer. FIG. 19 shows an example of a semiconductor device. In FIG. 19, 10a is a ceramic circuit board. 20 is a semiconductor device. 21 is a semiconductor element. 22 is a bonding layer. 23 is a wire bonding. 24 is a metal terminal. In FIG. 19, a semiconductor element 21 is bonded onto a metal plate of a ceramic circuit board 10a via a bonding layer 22. Similarly, a metal terminal 24 is bonded via a bonding layer 22. Adjacent metal plates are electrically connected to each other by a wire bonding 23. In FIG. 19, in addition to the semiconductor element 21, a wire bonding 23 and a metal terminal 24 are bonded. The semiconductor device according to the embodiment is not limited to such a structure. For example, only one of the wire bonding 23 and the metal terminal 24 may be provided. A plurality of semiconductor elements 21, bonding wires 23, and metal terminals 24 may be provided on the front metal plate 13. The semiconductor elements 21, bonding wires 23, and metal terminals 24 can be bonded to the back metal plate 18 as necessary. The metal terminals 24 can have various shapes, such as a lead frame shape or a convex shape. By using the brazing filler metal according to the embodiment in the above-mentioned ceramic circuit board or semiconductor device, for example, the reliability of these can be improved.
[0041] Although some embodiments of the present invention have been illustrated above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. Modifications of these embodiments are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. In addition, the above-mentioned embodiments can be implemented in combination with each other.
Claims
1. A method for manufacturing a bonded body in which a ceramic substrate and a copper plate are thermally bonded together using a brazing material, comprising the steps of: When the total amount of the raw materials contained in the brazing material is taken as 100 mass %, the brazing material contains Ag in an amount of more than 0 mass % and not more than 75 mass %, Cu in an amount of 15 mass % or more and not more than 85 mass %, Ti or TiH 2 and 1 mass% or more and 15 mass% or less of either Sn or In, Average Ag particle size D 50 is the average grain size of Cu, D 50 and the average particle size D of Sn or In is smaller than 50 Smaller than The method for producing a joined body, wherein the brazing material has an endothermic peak in a temperature range of 550° C. to 700° C. in a temperature rising step when a DSC curve is measured with a differential scanning calorimeter (DSC).
2. 2. The method for manufacturing a joint body according to claim 1, wherein the brazing material has a ratio of the mass of Ag to the mass of Cu of 1.3 or less.
3. 3. The method for manufacturing a joint body according to claim 1, wherein the brazing material has a mass ratio of Sn to Ag or a mass ratio of In to Ag of 0.25 or more.
4. 4. The method for producing a joined body according to claim 1, wherein the brazing filler metal has, when a DSC curve is measured with a differential scanning calorimeter (DSC), one or both of an endothermic peak and an exothermic peak within a range of 140° C. or more and 300° C. or less in the heating step.
5. 5. The method for producing a bonded body according to claim 1, wherein a bonding temperature when the ceramic substrate and the copper plate are heat-bonded by using the brazing material is 800[deg.] C. or less.
6. The joining temperature when the ceramic substrate and the copper plate are heated and joined by using the brazing material is higher than the temperature of the largest endothermic peak in the temperature increasing step, which is in the range of 550° C. or more and 650° C. or less; 6. The method for manufacturing a bonded body according to claim 1, wherein a difference between the bonding temperature and the temperature of the largest endothermic peak is 50° C. or more and 100° C. or less.
7. 7. The method for manufacturing a joint body according to claim 1, wherein the brazing material has two or more endothermic peaks within a temperature range of 550° C. to 650° C. in the temperature increasing step.
8. 8. The method for producing a joined body according to claim 1, wherein the endothermic peak occurring at 550° C. or more and 650° C. or less in the temperature-raising step is greater than the endothermic peak occurring at 700° C. or more in the temperature-raising step.
9. 9. The method for producing a bonded body according to claim 1, wherein the temperature increasing step has an endothermic peak in a range of 450° C. or more and 520° C. or less.
10. 10. The method for manufacturing a bonded body according to claim 1, wherein the ceramic substrate is a silicon nitride substrate, and the copper plate has a thickness of 0.3 mm or more.
11. 11. The method for manufacturing a bonded body according to claim 1, wherein the ceramic substrate has a length of 200 mm or more and a width of 200 mm or more.
12. 12. A method for producing a ceramic circuit board, comprising the step of providing a circuit shape to the copper plate of a bonded body obtained by the method for producing a bonded body according to any one of claims 1 to 11.
Citation Information
Patent Citations
Paste composition for jointing between ceramic and metal
JP1993139856A
Brazing material for joining ceramic-copper
JP1999130555A
Method of joining ceramic body to copper plate
JP2003055058A
Nitride based ceramic circuit board
JP2014091673A
Method for coating surfaces with hard substances
US4749594A